Green Marketing terhadap Keputusan Pembelian pada Moto Kopi di Denpasar dengan Brand Image sebagai Variable Mediasi - Budiatha, I Made Augie Putra; Ariwangsa, I Gusti Ngurah Oka; Martini, I. A. Oka; Putra, Komang Widhya Sedana (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid expansion of Indonesia’s coffee shop industry has been accompanied by growing consumer concern for sustainability. However, previous studies on green marketing show inconsistent results, particularly regarding its direct effect on purchasing decisions and the mediating role of brand image. This study aims to examine how green marketing influences purchasing decisions at Moto Kopi Denpasar and to assess whether brand image strengthens this relationship. A quantitative approach was employed using a structured questionnaire distributed to 130 consumers selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect effects. The results show that green marketing has a significant positive impact on purchasing decisions and also enhances brand image. Furthermore, brand image significantly affects purchasing decisions and partially mediates the relationship between green marketing and purchasing behavior. These findings indicate that sustainability-oriented marketing practices not only shape consumer perceptions but also reinforce their decision-making process. The study highlights the importance of building a credible environmentally responsible image to strengthen consumer responses in a competitive coffee shop market.